2003
DOI: 10.1055/s-2003-45426
|View full text |Cite
|
Sign up to set email alerts
|

Concept for Diagnosis and Therapy of Unilateral Recurrent Laryngeal Nerve Paralysis Following Thoracic Surgery

Abstract: RLNP following thoracic surgery requires immediate diagnosis and therapeutic strategy to minimize postoperative complications and to overcome impairments in the voice, swallowing, and coughing. The interdisciplinary concept presented in this study is especially advisable in high-risk RLNP procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In addition, when a R-DLT is inserted into a patient’s airway, body heat may decrease the stiffness of the DLT. In a previous study, warming the distal part of the DLT appeared to be effective for reducing some airway complications [ 16 , 17 ] . A previous study reported that 3% of the patients were hoarse for more than 5 postoperative days [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when a R-DLT is inserted into a patient’s airway, body heat may decrease the stiffness of the DLT. In a previous study, warming the distal part of the DLT appeared to be effective for reducing some airway complications [ 16 , 17 ] . A previous study reported that 3% of the patients were hoarse for more than 5 postoperative days [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have shown that the RLN nerve can partly regenerate months after surgery,1, 8 postoperative dysfunction such as dysphagia and water aspiration after RLN injury can lead to severe complications, including lung infection or even asphyxia, which may be fatal in certain patients. In patients who present with symptoms of nerve invasion, commonly regarded as a contraindication of surgery, nerve reconstruction can be considered to improve the symptoms if chemotherapy or radiotherapy has failed.…”
Section: Discussionmentioning
confidence: 99%
“…Subaortic and para‐aortic lymph nodes should be dissected for lung cancers in the left lung. Therefore, the left RLN is more frequently exposed to injury during subaortic and para‐aortic lymph node or tumor dissection because of its path around the aortic arch 1. The reported incidence of RLN injuries from esophagus and lung surgery varies greatly.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations